Agricultural cooperatives as a mechanism to strengthen the solidarity and social economy and achieve territorial development in the Tafrata Plain in northeastern Morocco - Bouguelba, Smail; El-Kallouchi, Mohamed (Journal of Humanities & Social Sciences, 2025)
The solidarity economy has evolved in the Tafrata Plain in northeastern Morocco in response to the increasing needs of individuals in the rural area, which accompanied the transformation of the socio-economic system from pastoralism to irrigated and rain-fed agriculture. Therefore, the solidarity economy that includes agricultural cooperatives in the area came as a response to the renewed socio-economic needs of farmers, and this type of economy that includes agricultural cooperatives in the Tafrata Plain is supposed to be an effective and efficient mechanism to achieve territorial development, considering that cooperative work is a territorial factor and a socio-economic choice to achieve territorial development. The study focuses on the spatial impact of the work of agricultural cooperatives and monitors their numbers, their temporal development, the proportion of their members, and the socio-economic results of their projects. The study aims to shed light on the extent to which the solidarity social economy can reduce the crises suffered by the agricultural sector in the Tafrata plain by adopting a scientific field approach aimed at studying models of local agricultural cooperative organizations and revealing the reality of the solidarity social economy in the region and its actual impact on achieving territorial development. This study is of great importance, especially given the urgent need to adopt an alternative economic model capable of promoting sustainability and social cohesion, especially considering the challenges facing the agricultural field. To achieve these objectives, the historical, descriptive and scientific analytical method was used. The results of the study showed the diversity of the participation of the social and solidarity economy in organizing the agricultural field, and the cooperative model plays a pivotal role in alleviating social and spatial issues despite its limited interventions and multiple issues. Therefore, to develop cooperative work, it is necessary for all local actors to develop action plans to implement SSE initiatives.
Keywords: Tafrata Plain; solidarity and social economy; agricultural cooperatives; territorial development